2021
DOI: 10.3390/microorganisms9081662
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Nitrogenase Structural and Assembly Components Reveals New Insights into the Origin and Distribution of Nitrogen Fixation across Bacteria and Archaea

Abstract: The phylogeny of nitrogenase has only been analyzed using the structural proteins NifHDK. As nifHDKENB has been established as the minimum number of genes necessary for in silico prediction of diazotrophy, we present an updated phylogeny of diazotrophs using both structural (NifHDK) and cofactor assembly proteins (NifENB). Annotated Nif sequences were obtained from InterPro from 963 culture-derived genomes. Nif sequences were aligned individually and concatenated to form one NifHDKENB sequence. Phylogenies obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…BuS5 in NCBI taxonomy), Desulfatiglandaceae and Syntrophales known to degrade alkanes or aromatic hydrocarbons coupled with sulfate reduction 7 , 57 . The increased diversity of bacterial and archaeal diazotrophic lineages substantially broadens the genomic database of microbial diazotrophs in deep-sea cold seep sediments 48 , which previously only included ANME-2b and SEEP-SRB1g 34 . Indeed, to our knowledge, this represents the first genomic evidence of nitrogen fixation potential in five different phyla, namely Altarchaeia, Omnitrophota, Caldatribacteriota along with two bacterial candidate phyla FCPU426 and UBA6262 48 , 58 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BuS5 in NCBI taxonomy), Desulfatiglandaceae and Syntrophales known to degrade alkanes or aromatic hydrocarbons coupled with sulfate reduction 7 , 57 . The increased diversity of bacterial and archaeal diazotrophic lineages substantially broadens the genomic database of microbial diazotrophs in deep-sea cold seep sediments 48 , which previously only included ANME-2b and SEEP-SRB1g 34 . Indeed, to our knowledge, this represents the first genomic evidence of nitrogen fixation potential in five different phyla, namely Altarchaeia, Omnitrophota, Caldatribacteriota along with two bacterial candidate phyla FCPU426 and UBA6262 48 , 58 .…”
Section: Resultsmentioning
confidence: 99%
“…2 ) suggested that nifH homologues were classified into distinct bona fide nitrogenase sequences (canonical groups I to III) as well as nitrogenase-like groups (groups IV to VI) 44 48 . These include (1) typical Mo-Fe nitrogenases from aerobic and facultative anaerobic bacteria (group I; n = 1); (2) Mo-Fe nitrogenases from anaerobic bacteria and archaea (group II; n = 32); (3) alternative nitrogenases (Mo-independent Anf and Vnf) and some Mo-Fe nitrogenases from Euryarchaeota 48 (group III; n = 11); (4) poorly characterized nif homologues (group IV; n = 123); (5) bacteriochlorophyll and chlorophyll biosynthesis genes 49 (group V; n = 1); and (6) putative tetrapyrrole cofactor biosynthesis genes 44 (group VI; n = 5). Group IV genes include its subclusters B ( n = 19), C ( n = 19) and E ( n = 16) with unknown functions, as well as subcluster D ( n = 69) involved in archaeal methionine biosynthesis 44 48 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reports verify the difficulty in attaining complete coverage of the nifH gene population, with over 50 primer sets described in the literature [ 58 ]. There is simply no sufficiently conserved region in the prokaryotic nifH gene pool [ 59 ]. The degenerate PCR primers that must be used can cause template-specific bias and require challenging annealing temperatures [ 60 ].…”
Section: Discussionmentioning
confidence: 99%